The Impact of Cost of Capital on Financial Performance: Evidence from Listed Non-Financial Firms in Nigeria (Global Business Management Review (GBMR), 2021)
This study examines whether Cost of Capital (COC) impact on the financial performance of listed non-financial firms in Nigeria for the period 2015-2019. Using two-step system Generalised Method of Moments (GMM), the study found a significant and negative impact of COC on financial performance of listed non-financial firms in Nigeria. This is because profitable firms have the opportunity to finance new investments with retained earnings rather than through a new debt and/or equity issuance. Also, raising the debt level of a firm may result in an increase in distress costs, and as such reduces benefits from the tax shield which consequently result in decline in the value of the firm. Thus, the finding of this study is in line with the pecking order theory of capital structure. The findings, which add to the existing knowledge with regard to the impact of COC on financial performance, should be interesting to the providers of finance. This is because the study helps them to make the decision whether or not to invest in these firms. Since they want their money to be invested where there will be maximum return. However, this result only hold for emerging economies like Nigeria where analyst cash flow forecast is difficult to predict. This is due to the underdeveloped nature of the capital market.